Vernacularization In The Sasak Language Translation Of The Qur'an (A Study Of Juz ‘Amma Al-Majidi) - Ahmad Askar (ASTEEC, 2023)
Sasak Language Translation of the Al-Qur'an (Juz 'Amma al-Majidi) is a translation of the Al-Qur'an which aims to combine and connect the Al-Qur'an with cultural elements of the Sasak people that have been developed and inherited. hereditary. The method used is literature analysis using a historical approach. Thus, this research produced three findings, namely: 1) The form of vernacularization found in the Sasak Language Translation of the Al-Qur'an is the mention of God with the term